السياحة الصحراوية في الجنوب الليبي البعد الاقتصادي والافاق المستقبلية - فائدة احمد سالم سعيد (Surman Journal of Science and Technology, 2024)
The Libyan desert abounds with an unlimited balance of diverse tourist attractions that are integrated together to form a tourism product that qualifies it to occupy an important position among the tourist countries at the level of the region and the world, as most of the Libyan territories fall within the scope of the desert region, which is estimated at about 91% of the total area of the country .This tourist attraction to the Libyan desert is due to a variety of factors, the most important of which is the large number of historical, artistic, cultural, natural and geographical attractions that characterize it. All this led to the distinctiveness of desert tourism in Libya, and desert tourism is a tool for economic, social and cultural development, as it contributes to diversifying sources of income for the national economy and improving the balance of payments as well as providing hard currency, as well as eliminating many economic issues, most notably unemployment. Accordingly, this study will be concerned with diagnosing the current reality of desert tourism in southern Libya, studying the obstacles and difficulties that prevent the development of this vital sector, anticipating the future prospects for desert tourism in southern Libya, then try to reach solutions and suggestions that would overcome the difficulties that stand in the way of the development of desert tourism in southern Libya.